Implementation of Spiritual Education in Generation Z Students - Mirza Mahbub Wijaya; Duwi Miyanto (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2022)
People born in today's information technology era between 1995 and 2010 are commonly referred to as generation Z (gen Z), namely teenagers born in the digital generation who enjoy the wonders of internet technology. They are proficient in information technology and various computer applications and can easily and quickly access information for educational or personal purposes. They live with smartphones and are very busy with social media. Information technology providing convenience has significantly impacted the way of life of young people from generation Z. Many teenagers cannot control themselves, use information technology in a defective manner, and encourage them to be involved in juvenile delinquency. This study aims to describe and develop learning formulas for generation z in the modern era. This research uses the literature review method, in which the study focuses on domestic and foreign literature. A literature review is a research method that collects data from various literary sources, which are then analyzed to obtain the required information. The results of the literature review found that the concept of spiritual education for generation Z requires efforts in the form of a school with an integrated system with a model of character and spiritual development or integration of faith and practice.(Orang-orang yang lahir di era teknologi informasi dewasa ini dalam rentang antara 1995 sampai 2010 biasa disebut sebagai generasi Z (gen Z), yaitu remaja yang lahir di generasi digital dan menikmati keajaiban teknologi internet. Mereka mahir teknologi informasi dan berbagai aplikasi komputer serta dengan mudah dan cepat mengakses informasi untuk kepentingan pendidikan atau pribadi. Mereka hidup dengan telepon cerdas (smartphone) dan sangat sibuk dengan media sosial Selain memberi kemudahan, teknologi informasi ternyata menimbulkan dampak signifikan terhadap cara hidup remaja dari generasi Z ini. Bahkan banyak remaja tidak dapat mengendalikan diri, menggunakan teknologi informasi secara menyimpang, dan mendorong mereka terlibat dalam kenakalan remaja. Studi ini bertujuan untuk mendeskripsikan dan mengembangkan formula pembelajaran untuk generasi z di era modern. Studi penelitian ini menggunakan metode kajian kepustakaan, di mana kajiannya berfokus pada literatur dalam negeri juga literatur asing. Kajian kepustakaan merupakan salah satu bentuk metode kajian yang dilakukan dengan mengumpulkan data dari berbagai sumber literatur yang kemudian dianalisis untuk mendapatkan sumber informasi yang dibutuhkan. Hasil dari kajian literatur menemukan bahwa konsep pendidikan spiritual untuk generasi Z memerlukan usaha berupa sekolah dengan sistem terpadu dengan model pengembangan karakter dan spiritual atau integration of faith and practice).